Development and analysis of pulse detonation engine (PDE) with fuel-air premixed intake system [electronic resource] - Abdul Hafiz Nor Hassan, 1985-, author; Mazlan Abdul Wahid, supervisor; Fakulti Kejuruteraan Mekanikal (2015)
Thesis (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2015